A highly sensitive hemicyanine-based fluorescent chemodosimeter for mercury ions in aqueous solution and living cells1. Issue 100 (29th October 2015) - Chen, Yu; Yang, Chengyu; Yu, Zhenni; Chen, Bo; Han, Yifeng
<x xml:space="preserve">Abstract</x> A novel hemicyanine-based fluorescence turn-on chemodosimeter for Hg2+ by mercury triggered hydrolysis of vinyl ether group has been reported.